'Carried to his last rest': public funerals as Jewish/non-Jewish spaces in modern Stockholm. Issue 1 (2nd January 2020) - Hultman, Maja
ABSTRACT: 20 Swedish-Jewish elite funerals between 1870 and 1939 presented individual combinations of Judaic, bourgeois, Christian, national and modern affiliations through their ritual and musical practices, performing a fragmented Jewishness to a partly non-Jewish audience, partly aided by non-Jewish soloists, musicians and eulogists. As locations for funeral services, the synagogue, the street and the cemetery were placed on the conceptual 'frontier' of Jewish/non-Jewish interaction, and thus functioned as temporary, public spaces for the renegotiation of the Jewish elite's position in the Swedish society. Consequently, Jewish elite funerals allowed for the temporary coexistence of Jewish distinctiveness and national belonging.